Extensive Morphea Following Adjuvant Radiotherapy for Breast Carcinoma—Case Report - Panaitescu, Alexandru; Nguyen, Hannah; Masson-Côté, Laurence; Fernandes, Carolina Lucena (Current oncology (Toronto), 2025)
Radiation-induced morphea (RIM) is a rare complication following radiotherapy (RT) for breast cancer treatment. Its distribution is usually confined to the breast having received radiotherapy. A generalized form of RIM also exists, defined as lesions extending beyond the radiotherapy site, but data on the subject are scarce in the literature. This complication remains difficult to treat, due partly to the variable extent of disease and to individual clinical response rates to the wide array of available therapies, such as topical therapy (i.e., topical tacrolimus or topical corticosteroids), phototherapy, and systemic therapy (i.e., systemic immunosuppressants). We present a case of extensive morphea post RT for breast cancer with 2 years of favorable evolution under systemic therapy.